Find the best answers to your questions at Westonci.ca, where experts and enthusiasts provide accurate, reliable information. Get immediate answers to your questions from a wide network of experienced professionals on our Q&A platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
Let's solve the problem step-by-step.
Given the polynomial function:
[tex]\[ P(x) = x^2 - 5x + 1 \][/tex]
1. Find [tex]\( P(2) \)[/tex]
Substitute [tex]\( x = 2 \)[/tex] into the polynomial:
[tex]\[ P(2) = 2^2 - 5(2) + 1 \][/tex]
Simplify the expression step-by-step:
[tex]\[ P(2) = 4 - 10 + 1 \][/tex]
[tex]\[ P(2) = -6 + 1 \][/tex]
[tex]\[ P(2) = -5 \][/tex]
Therefore, [tex]\( P(2) = -5 \)[/tex].
2. Find [tex]\( P(-1) \)[/tex]
Substitute [tex]\( x = -1 \)[/tex] into the polynomial:
[tex]\[ P(-1) = (-1)^2 - 5(-1) + 1 \][/tex]
Simplify the expression step-by-step:
[tex]\[ P(-1) = 1 + 5 + 1 \][/tex]
[tex]\[ P(-1) = 7 \][/tex]
Therefore, [tex]\( P(-1) = 7 \)[/tex].
3. Find [tex]\( P(2) + P(-1) \)[/tex]
Now, we add the values of [tex]\( P(2) \)[/tex] and [tex]\( P(-1) \)[/tex]:
[tex]\[ P(2) + P(-1) = -5 + 7 \][/tex]
Simplify the expression:
[tex]\[ P(2) + P(-1) = 2 \][/tex]
Therefore, the final answers are:
[tex]\[ P(2) = -5 \][/tex]
[tex]\[ P(-1) = 7 \][/tex]
[tex]\[ P(2) + P(-1) = 2 \][/tex]
Given the polynomial function:
[tex]\[ P(x) = x^2 - 5x + 1 \][/tex]
1. Find [tex]\( P(2) \)[/tex]
Substitute [tex]\( x = 2 \)[/tex] into the polynomial:
[tex]\[ P(2) = 2^2 - 5(2) + 1 \][/tex]
Simplify the expression step-by-step:
[tex]\[ P(2) = 4 - 10 + 1 \][/tex]
[tex]\[ P(2) = -6 + 1 \][/tex]
[tex]\[ P(2) = -5 \][/tex]
Therefore, [tex]\( P(2) = -5 \)[/tex].
2. Find [tex]\( P(-1) \)[/tex]
Substitute [tex]\( x = -1 \)[/tex] into the polynomial:
[tex]\[ P(-1) = (-1)^2 - 5(-1) + 1 \][/tex]
Simplify the expression step-by-step:
[tex]\[ P(-1) = 1 + 5 + 1 \][/tex]
[tex]\[ P(-1) = 7 \][/tex]
Therefore, [tex]\( P(-1) = 7 \)[/tex].
3. Find [tex]\( P(2) + P(-1) \)[/tex]
Now, we add the values of [tex]\( P(2) \)[/tex] and [tex]\( P(-1) \)[/tex]:
[tex]\[ P(2) + P(-1) = -5 + 7 \][/tex]
Simplify the expression:
[tex]\[ P(2) + P(-1) = 2 \][/tex]
Therefore, the final answers are:
[tex]\[ P(2) = -5 \][/tex]
[tex]\[ P(-1) = 7 \][/tex]
[tex]\[ P(2) + P(-1) = 2 \][/tex]
We appreciate your time. Please come back anytime for the latest information and answers to your questions. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.